Animal diversity - Hickman, Cleveland P. Jr.; Roberts, Larry S.; Keen, Susan L.; Larson, Allan; Eisenhour, David J. (New York McGraw-Hill Education, 2015)
This text provides a concise introduction to the field of animal biology. After these introductory chapters, readers delve into the biology of all groups of animals. Chapter highlights include newly discovered features of animals as they relate to ecology, conservation biology, and value to human society.
1. Science of zoology and evolution of animal diversity -- 2. Animal ecology -- 3. Animal architecture -- 4. Taxonomy and phylogeny of animals -- 5. Unicellular eukaryotes -- 6. Sponges: phylum porifera -- 7. Cnidarians and ctenophores -- 8. Acoelomorpha, platyzoa, and mesozoa: flatworms, gastrotrichs, gnathiferans, and mesozoans -- 9. Polyzoa and kryptrochozoa: cycliophora, entoprocta, ectoprocta, brachiopoda, phoronida, and nemertea -- 10. Molluscs -- 11. Annelids and allied taxa -- 12. Smaller ecdysozoans -- 13. Arthropods -- 14. Chaetognaths, echinoderms, and hemichordates -- 15. Vertebrate beginnings: the chordates -- 16. Fishes -- 17. The early tetrapods and modern amphibians -- 18. Amniote origins and nonavian reptiles -- 19. Birds -- 20. Mammals.
Keywords: Zoology; Animal diversity